2021
DOI: 10.3389/fpls.2021.697988
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Signaling Facilitates Plant Adaption to Physical Barriers

Abstract: The morphological changes are usually observed in the terrestrial plants to respond to physical barriers. The phytohormone ethylene plays an essential role in the morphological development of plants encountering exogenous mechanical impedance, which enables plants to grow optimally in response to physical barriers. Ethylene is shown to regulate these developmental processes directly or in concert with other phytohormones, especially auxin. In this mini review, the involvement of ethylene action in seedling eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…However, removal of the distal 2 cm of the 3‐cm‐long pedicels dramatically increased ethylene sensitivity of “Miss Teen.” This suggests that the pedicel is important for the ethylene insensitivity of abscission in “Miss Teen.” It was concluded that the abscission zone (AZ) in “Miss Teen” became rapidly insensitive to ethylene at the time of flower opening (Bunya‐atichart et al., 2006). Ethylene is reported to trigger ethylene responses by first binding to the endoplasmic reticulum‐localized receptors, including ethylene response 1 ( ETR1 ), ethylene response sensor 1 ( ERS1 ), ETR2 , ERS2 , and ethylene insensitive 4 ( EIN4 ) to inhibit these receptors from interacting with and activating the negative ethylene signaling regulator constitutive triple response 1 ( CTR1 ) (Binder, 2020; Guo & Ecker, 2004; Liu & Chen, 2021). It would be interesting to determine if sensitivity to ethylene within the pedicel of ‘"Miss Teen"’ changes in accordance with these ethylene receptor genes.…”
Section: Postharvest Physiologymentioning
confidence: 99%
“…However, removal of the distal 2 cm of the 3‐cm‐long pedicels dramatically increased ethylene sensitivity of “Miss Teen.” This suggests that the pedicel is important for the ethylene insensitivity of abscission in “Miss Teen.” It was concluded that the abscission zone (AZ) in “Miss Teen” became rapidly insensitive to ethylene at the time of flower opening (Bunya‐atichart et al., 2006). Ethylene is reported to trigger ethylene responses by first binding to the endoplasmic reticulum‐localized receptors, including ethylene response 1 ( ETR1 ), ethylene response sensor 1 ( ERS1 ), ETR2 , ERS2 , and ethylene insensitive 4 ( EIN4 ) to inhibit these receptors from interacting with and activating the negative ethylene signaling regulator constitutive triple response 1 ( CTR1 ) (Binder, 2020; Guo & Ecker, 2004; Liu & Chen, 2021). It would be interesting to determine if sensitivity to ethylene within the pedicel of ‘"Miss Teen"’ changes in accordance with these ethylene receptor genes.…”
Section: Postharvest Physiologymentioning
confidence: 99%
“…It has been reported that ethylene inhibits hypocotyl elongation in darkness while promoting its growth in light (Zhong et al, 2012). For Arabidopsis seedling establishment under the soil, ethylene interacts with diverse hormone pathways to suppress and/or promote hypocotyl growth and enables seedlings to penetrate through the soil layers more easily (Liu & Chen, 2021; Zhong et al, 2014).…”
Section: Ethylene Regulates Coleoptile Elongation In Different Monoco...mentioning
confidence: 99%
“…Ethylene triggers ethylene responses by first binding to the endoplasmic reticulum-localized receptors ethylene response 1 (ETR1), ethylene response sensor 1 (ERS1), ETR2, ERS2, and ethylene insensitive 4 (EIN4) to inhibit these receptors from interacting with and activating the negative ethylene signaling regulator constitutive triple response 1 (CTR1; Bleecker, 1999;Chang and Shockey, 1999;Alonso and Stepanova, 2004;Merchante et al, 2013;Ju and Chang, 2015;Yang et al, 2015;Azhar et al, 2019;Binder, 2020;Zhao et al, 2020;Liu and Chen, 2021). The inhibition of the interaction for receptors to CTR1 causes the activation of several positive regulators of the ethylene response downstream of CTR1, including EIN2, EIN3, ethylene response DNA-binding factor 1-4 (EDF1-4), and ethylene response factors (ERFs), resulting in downstream ethylene responses.…”
Section: Introductionmentioning
confidence: 99%
“…The ethylene response DNA-binding factor (EDF) family and ERF are transcription factors involved in ethylene signal transduction (Stepanova and Alonso, 2005;Chen et al, 2021). In the absence of ethylene, these ethylene receptors (ETR1, ERS1, ETR2, ERS2, and EIN4) can activate CTR1 and suppress ethylene signaling (Binder, 2020;Zhao et al, 2020;Liu and Chen, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation